Diabetes distress and marriage in Type-1 diabetes - Deepak Khandelwal; Lovely Gupta; Sanjay Kalra; Amit Vishwakarma; Priti Rishi Lal; Deep Dutta (Wolters Kluwer Medknow Publications, 2018)
Background: In spite of the large number of people with Type-1 diabetes mellitus (T1DM) in India, India is not a diabetes-friendly society. The society suffers from lots of myths regarding diabetes and insulin use. This review highlights challenges faced by young people living with T1DM with regards to marriage, associated diabetes distress, and suggests potential solutions. Methods: PubMed, Medline, and Embase search for articles published up to October 2017, using the terms "marriage" (MeSH Terms) OR "diabetes distress" (All Fields) OR "depression" (All Fields) AND "diabetes" (All Fields). The reference lists of the articles thus identified were also searched. The search was not restricted to English-language literature. Results: Misconception regarding social, occupational, marital abilities, fertility, genetics, quality of life, sexism in young people living with T1DM raises major barriers to marriage, resulting in significant diabetes distress, depression, and psychological issues in them. People with T1DM are wrongly assumed to be sick, disabled, dependent persons, unsuitable for marriages, and likely to have complicated pregnancies with the possibility of having children with diabetes. Counseling at the level of individual, spouse, family, and society can help in obviating such issues. Conclusion: Diabetes distress and psychological issues are major problems related to marriage in young people with T1DM. Counseling of patients, family, relatives, prospective spouse, and increasing social awareness regarding diabetes through mass communication are the keys to their resolution.